Avaliação do impacto das mudanças climáticas no balanço hídrico na bacia do Orós usando os modelos de mudanças climáticas do IPCC-AR4 para o cenário A1B - Fernandes, Wescley de Sousa (2016)
Projections flows to the basin of Orós - Ceará were obtained using the precipitation of global mo-dels of the fourth report of the Intergovernmental Panel on Climate Change (IPCC AR4-) for the period 2010-2099 the A1B scenario. It can be observed both a quantitative superiority as a qualitative superiority of the fourth report of the data before the fifth report, a decisive factor for choosing such a report in the construction of the results, where the proper handling of data is critical. Another determining factor in the choice of the fourth report was the range of referential work, guiding factor in comparison of results. Flows were generated by the hydrological model Soil Moisture Account Procedure (SMAP), initializing by rainfall corrected statistically from observed data and evaporation estimated by the Penman-Montheith method. To analyze the impact on the annual average flow of the XXI century was assessed the trend of the series using the Mann-Kendall-Sen method. To identify the frequency of extreme events we compared the distribution curves of acu-mulada probability of the twentieth and twenty-first century. For seasonal analysis considered the anomaly in the average weather of the twenty-first century designs for the twentieth century. In terms of seasonal projections can observe a small dispersion of the models along with a monthly increase of the potential evaporation, achieving a difference of up to 53.47 %. For the seasonality of flows, it was observed greatest impact in the months of the rainy season, resulting in a possible shift of the ITCZ to further north or further south.